Automatic Impedance Double-Stub Tuner for High-Power S-Band Microwave Networks - Kommey, Benjamin; Addo, Ernest Ofosu; Tamakloe, Elvis (CHIPSET, 2025)
This paper presents the development of an impedance tuner realized in the WR-340 waveguide for use in S-band networks (2.45 GHz ISM band). The tuner is a double-stub structure designed to be adjoined to a reflectometer and performs automatic impedance matching using the reflectometer’s measurements through a closed-loop feedback mechanism. The device is designed to work under the full operating conditions of high-power microwave generators. Simulations and preliminary measurements show that the impedance tuner performance is stable and temperature independent. The system is suited for on-line monitoring and control of network parameters in industrial waveguide applications